Wear behaviour analysis of medium carbon high silicon alloy steel at different process parameter. Issue 2 (2nd April 2020) - Kumar, Rajan; Dwivedi, Ravi Kumar; Ahmed, Siraj; Singh, Anoop Pratap
ABSTRACT: In railway wheel, track and mechanical component major issue losses of material due to rolling contact and sliding contact. A dual-wear type wear testing machine has been designed and developed, in which two discs rotate perpendicular to each other in the same direction with different velocity. In this machine bot type of wear, we can calculate rolling as well as sliding. As a result, the outer most peripheries of these discs are in symmetrical rolling contact. Discs were made up of medium carbon high silicon alloy steel with different treatments performed and were rubbed against each other rolling and sliding wear test performed in dissimilar metal also. All combinations of discs were tested including the same metal pairs. In similar metal combinations, the wear characteristics depended on the surface properties and microstructure, but not on the material hardness. Wear characteristics of material test performed on different surface treated sample by self-developed dual-wear testing machine Experimental data listed in this research paper. Characterisation of material/samples with field emission scanning electron microscopy and atomic force microscopy.